2020
DOI: 10.3390/genes11080880
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Factor Transcript Abundance in Saliva as a Diagnostic Tool for Breast Cancer

Abstract: Breast cancer is the second leading cause of death in women above 60 years in the US. Screening mammography is recommended for women above 50 years; however, 22% of breast cancer cases are diagnosed in women below this age. We set out to develop a test based on the detection of cell-free RNA from saliva. To this end, we sequenced RNA from a pool of ten women. The 1254 transcripts identified were enriched for genes with an annotation of alternative pre-mRNA splicing. Pre-mRNA splicing is a tightly regulated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In total, 16 142 articles were identified in the aforementioned databases (Table 1). However, 234 articles were retained for full reading, following the elimination of duplicates and articles whose title and abstract did not meet the eligibility criteria; of these, only 136 12…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 16 142 articles were identified in the aforementioned databases (Table 1). However, 234 articles were retained for full reading, following the elimination of duplicates and articles whose title and abstract did not meet the eligibility criteria; of these, only 136 12…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 26 articles reported sensitivity and specificity figures greater than 70% for combined biomarkers in the form of panels 27,29,30,61,76,77,81,82,87,90,93,94,97,98,101,104,106,111-114,118,123,124,132,147 leaving only 6 panels with figures lower than 70%. 61,76,93,114,124,132 Finally, 27 articles reported AUC and P values, 26,62,63,67,71,72,78,83,84,88,102,110,116,120,122,125,127,130,133,135,137,139,140,142,143,145,146 and of these, AUC was lower than 0.7 67,133,1...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva is a body fluid that can be collected easily, quickly, and non-invasively ( 140 ). Biomolecules in saliva have been used as promising markers for early diagnosis, detection, and treatment in OSCC ( 141 , 142 ), breast cancer ( 143 , 144 ), OC ( 145 ), and other tumors. In OSCC, saliva is the body fluid that has the closest contact with oral tumors.…”
Section: Salivamentioning
confidence: 99%
“… 79 Xu et al subsequently showed that the expression of four mRNA biomarkers in saliva were significantly downregulated in GC patients compared to healthy controls. 80 Besides, salivary mRNA biomarkers has been explored in breast cancer, 81 ovarian cancer, 82 lung cancer, 83 and chronic myeloid leukemia. 84 Most of those studies indicated that combined analysis of salivary mRNA biomarkers and other known biomarkers could improve the performance of cancer detection.…”
Section: Introductionmentioning
confidence: 99%